Numerical study of the mixed spin-1 and spin-5/2 BEG model on the Bethe lattice - YESSOUFOU, RACHIDI ADENIYI AKAMBI; SMAINE, Bekhechi; HONTINFINDE, FÉLIX (My University, 2011)
The mixed spin-1 and spin- 5 ferromagnetic Ising model with bilinear (J) and biquadratic (K) 2 nearest-neighbor exchange interactions and a single-ion potential or crystal-field interaction (D) is studied on the Bethe lattice by means of exact recursion equations. First, the phase diagram of the system at zero temperature is obtained in the (D/Jq, K/Jq) plane, where q denotes the coordination number of the lattice. Second, the sublattice magnetizations as functions of the temperature, the crystal-field and the biquadratic interaction strengths are thoroughly investigated. For q = 3, the resulting phase diagrams show first and second order phase transitions as well as compensation points where the net magnetization of the whole lattice should vanish in the antiferromagnetic version of the model. One interesting feature of the model concerns the presence of tricritical points. Our calculations show that at non-zero temperature, none of the sublattice can order separately. However, under an external magnetic field, some interesting phase diagrams with partially ordered phases arise.
Keywords: mixed spin model • Bethe lattice • recursion relations • magnetization • phase transition